Geographic information systems and public health : eliminating perinatal disparity - Curtis, Andrew, 1967-; Leitner, Michael, 1965- (Hershey, PA : IRM Press, 2006)
'This book provides an overview of why geography is important in the investigation of health, the importance of the main components of a GIS, how important neighborhood context is when using a GIS, and the general differences found between urban and rural health environments' -- Provided by publisher
Includes bibliographical references and index
Keywords: Geographic information systems; Public health -- Data processing